Preparation and application of patterned hollow-fiber membranes to membrane bioreactor for wastewater treatment - Kim, Inae; Choi, Dong-Chan; Lee, Jaewoo; Chae, Hee-Ro; Jang, Jun Hee; Lee, Chung-Hak; Park, Pyung-Kyu; Won, Young-June (ELSEVIER SCIENCE BV, 2015)
Hollow-fiber membranes have been widely used in membrane processes for water and wastewater treatments, but membrane fouling in commercialized hollow-fiber membranes still remains a challengeable task to be solved. In this study, we introduced patterned morphology to the membrane surface of a polyvinylidene fluoride (PVDF) hollow-fiber module using a lithographic method. Two types of patterned hollow-fiber (PHF) PVDF membranes (prism and pyramid) were prepared respectively, and their anti-biofouling characteristics were tested in a membrane bioreactor (MBR) for wastewater treatment. PHF membranes with high pattern fidelity were fabricated under the pressurized injection of the non-solvent for phase inversion. The PHFs showed not only higher water flux due to the increase of the effective membrane surface, but also enhanced anti-fouling property in comparison to a non-patterned hollow-fiber membrane. The effect of the PVDF concentration and non-solvent injection rate were also investigated on the morphology and pattern fidelity of PHF membranes. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SOFT LITHOGRAPHY